Effects of desurfacing of alfisols and ultisols in Southern Nigeria: I. crop performance - Mbagwu, J.S.C.; Lal, R.; Scott, J. (1984)
The widespread incidence of soil erosion in the tropics has been reported but few studies have dealt with the specific problem of decline in crop productivity associated with the soil loss. An understanding of the effect of topsoil loss on crop yield is needed in order to develop some management practices for restoring productivity on eroded soils. The effects of topsoil removal on maize (Zea mays L.) and cowpea (Vigna unguiculata L.) grain yields and their response to N and P rates were investigated in one double cropping sequence on an Ultisol at Onne in southeast Nigeria, and two Alfisols at Ikenne and Ilora in southwest Nigeria. In comparison with unfertilized uncut control, maize grain yield was reduced by 95.4, 95.4, and 100% at Onne, 30.5, 73.6, and 93.5% at Ikenne, and 72.5, 82.6, and 99.5% at Ilora for 5‐, 10‐, and 20‐cm soil depths removed, respectively. Cowpea yield reductions were 62.7, 70.6, and 68.3% at Onne, 1.5, 59.1, and 65.1% at Ikenne and 42.6, 33.1, and 80.5% at Ilora for 5, 10, and 20 cm of soil removal, respectively. None of the fertilizer combinations used was an effective substitute for topsoil removed at Onne during the two seasons and at Ilora during the second season. The rate of 60 and 120 kg N ha−1 in combination with 30 kg P ha−1 restored maize yield at Ikenne equivalent to or within 4% of the control for 5 cm soil removed. At Ilora combinations of 60 and 120 kg N ha−1 and 15 and 30 kg P ha−1 produced maize grain yields equivalent to or within 43% of control where 5 cm soil was removed.